Persistence and evolution of linezolid- and methicillin-resistant Staphylococcus epidermidis ST2 and ST5 clones in an Italian hospital - Marzia Cinthi; Sonia Nina Coccitto; Antonella Pocognoli; Guido Zeni; Annarita Mazzariol; Alessandra Di Gregorio; Carla Vignaroli; Andrea Brenciani; Eleonora Giovanetti (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Objectives: Staphylococcus epidermidis is a member of the human skin microbiome. However, in recent decades, multidrug-resistant and hospital-adapted S. epidermidis clones are increasingly involved in severe human infections associated with medical devices and in immunocompromised patients. In 2016, we reported that a linezolid- and methicillin-resistant S. epidermidis ST2 clone, bearing the G2576T mutation, was endemic in an Italian hospital since 2004. This study aimed to retrospectively analyse 34 linezolid- and methicillin-resistant S. epidermidis (LR-MRSE) strains collected from 2018 to 2021 from the same hospital. Methods: LR-MRSE were typed by Pulsed-Field Gel Electrophoresis and multilocus sequence typing and screened for transferable linezolid resistance genes. Representative LR-MRSE were subjected to whole-genome sequencing (WGS) and their resistomes, including the presence of ribosomal mechanisms of linezolid resistance and of rpoB gene mutations conferring rifampin resistance, were investigated. Results: ST2 lineage was still prevalent (19/34; 55.9%), but, over time, ST5 clone has been widespread too (15/34; 44.1%). Thirteen of the 34 isolates (38.2%) were positive for the cfr gene. Whole-genome sequencing analysis of relevant LR-MRSE displayed complex resistomes for the presence of several acquired antibiotic resistance genes, including the SCCmec type III (3A) and SCCmec type IV (2B) in ST2 and ST5 isolates, respectively. Bioinformatics and polymerase chain reaction (PCR) mapping also showed a plasmid-location of the cfr gene and the occurrence of previously undetected mutations in L3 (ST2 lineage) and L4 (ST3 lineage) ribosomal proteins and substitutions in the rpoB gene. Conclusion: The occurrence of LR-MRSE should be carefully monitored in order to prevent the spread of this difficult-to-treat pathogen and to preserve the efficacy of linezolid.